Energy storage enhancement of P(VDF-TrFE-CFE)-based composites with double-shell structured BZCT nanofibers of parallel and orthogonal configurations. (December 2019) - Zhang, Yue; Zhang, Changhai; Feng, Yu; Zhang, Tiandong; Chen, Qingguo; Chi, Qingguo; Liu, Lizhu; Wang, Xuan; Lei, Qingquan
Abstract: Recent research in the development of flexible polymer dielectric materials for the conversion of electrical energy is springing up. A state-of-the-art energy-storage polymer-based composite with the potential of improving the performances (energy-storage density and efficiency) at the low electric field strength is proposed here. The ferroelectric polymer P(VDF-TrFE-CFE) (PVTC) blending with linear polymethyl methacrylate (PMMA) is used as the matrix to ensure higher polarization and lower energy loss. Meanwhile, the inorganic 0.5Ba(Zr0.2 Ti0.8 )O3 -0.5(Ba0.7 Ca0.3 )TiO3 (BZCT) nanofibers work as the filler, and the double transition layers of core-shell structure (Al2 O3 +SiO2 ) serve as the interface. Finally, P(VDF-TrFE-CFE)-based composites with double-shell structured BZCT nanofibers of parallel and orthogonal configurations were fabricated. The effects of microstructure information (matrix, filler, interface) together with different configurations (parallel and orthogonal configurations) of BZCT@Al2 O3 @SiO2 nanofibers on the performances of nanocomposites were systematically and primarily discussed. Importantly, the Orthogonal BZCT@A@S⊥PVTC + PM composite with 3 vol% BZCT@A@S NFs possessed an excellent discharged energy density (~20.1 J/cm 3 ) with charge-discharge efficiency of ~58.6% at ~440 kV/mm; meanwhile, the in-plane thermal conductivity of it reaches to ~0.33 W/(m·K). Referring to the experimental findings and simulation results, a mechanism related to rapidly polarized ferroelectric filler was proposed. Graphical abstract: The dielectric nanocomposite with an excellent comprehensive performance in energy storage and thermal properties has been achieved by constructing the orthogonal configuration of hybrid double-shell BZCT@Al2 O3 @SiO2 nanofibers. Image 1 Highlights: The PVTC blending with PMMA as matrix provides the high polarization and the low energy loss for energy conversion. Large-aspect-ratio core of BZCT NFs with stronger dipole polarization enhance the polarization of polymer-based composite. Interface modification with double-shell contributes to the energy storage performance and thermal property of composite. BZCT@A@S-PVTC+PM composite with different configurations of BZCT@A@S NFs promotes the electric field redistribution. Thermal conductivity is improved by the aligned 1-D double-shell nanofibers in inorganic-organic polymer-based composite.